Relationship between corporate culture and competitive power of the companies in the tourism industry - Milena Kirilova Filipova (Tourism & Management Studies)
The major objective of this research is to clarify the contents implied in the concept “corporate culture”, to study the level of development of corporate culture and the formation of mission in the tourist companies in Bulgaria, to explore the psychological climate and motivation factors as well as to throw light upon the relationship between corporate culture and competitive power in tourism. The major research methods used in this work are the method of analysis and synthesis, method of comparison, and inquiry survey. The major outcomes achieved by this work are: 1. A clear distinction is made between the internal and external aspect of corporate culture in tourism; 2. The degree of development of corporate culture is established, as well as of the formation of a mission in the tourist companies in South Bulgaria; 3. The factors influencing the level of corporate culture in tourism are established; 4. The relationship between the corporate culture and the competitive power of tourism is clarified. These outcomes can be directly applied and used by the managers for the establishment of corporate culture or enhancement of its level in the tourism companies in South Bulgaria